PEMBINAAN KELOMPOK UMKM DI KABUPATEN SUMEDANG - Edi setiawan; Nur’alfiati, Diana Gustiana; Putra, Dicka Sunandar; Firmansyah, Muhamad; Hasanah, Nu’aini Siti; Drupada, Oktavia; Mulyana, Ujang (JRPA - Journal of Regional Public Administration, 2024)
This research aims to find out how MSME development is carried out in the Department of Cooperatives, Micro, Small and Medium Enterprises, Trade and Industry in Sumedang Regency, what factors hinder it and efforts to overcome the obstacles. The research method used in the research is qualitative methodology with four research informants. The data collection techniques used were literature study and field study consisting of observation, interviews and documentation. Meanwhile, the processing procedures in this research are data reduction, data presentation, data verification and data triangulation Based on the research results, it was concluded that the development of MSMEs in the Department of Cooperatives, Micro, Small and Medium Enterprises, Trade and Industry in Sumedang Regency can be said to be quite good, but there are still several obstacles. This occurs because of obstacles such as difficulties in the process of coaching employees and MSME actors, the arrangement of resources is not yet optimal, because it is seen from age limitations which affect the capabilities of human resources (HR) so that they do not match the abilities needed to form a team with the aim of to socialize the coaching that has been carried out, in efforts to improve the implementation of MSME coaching at the Department of Cooperatives, Micro, Small and Medium Enterprises, Trade and Industry, Sumedang Regency, the government should continue to carry out analysis, routine evaluation and supervision of coaching so that employees' needs continue to be monitored.